(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to investigate the prevalence of the hepatitis B virus and hepatitis C virus in patients undergoing hemodialysis in Karabuk city.Material and Methods: For patients presented to the Karabuk University Training and Research Hospital for hemodialysis between January 2016 and December 2018, HBsAg, anti-HBs, and anti-HCV assays were conducted using the chemiluminescence method and HBV DNA, HCV RNA and HCV genotyping tests were conducted using real-time polymerase chain reaction. The data was retrospectively evaluated.Results: Of 345 patients undergoing hemodialysis, 211 (61.2%) were male and 134 (38.8%) were female. The mean age of the patients was 62 (15–96) years. Moreover, 0.9% (n = 3) of patients were HBsAg positive and 4.3% (n = 15) were anti-HCV positive. Three patients with HBsAg positivity were also HBV DNA positive. Of the 15 patients who were anti-HCV positive, 12 were also HCV RNA positive. Of these, eight patients had the HCV genotype 1b and four patients had the genotype 4. Anti-HBs seropositivity was detected in 65.8% of patients. The highest Anti-HBs seropositivity rate was observed in patients aged 40 years (76%) and the difference between age groups was statistically significant (p = 0.002). Conclusion: In our study, the prevalence of HBsAg seropositivity in patients undergoing hemodialysis (0.9%) was lower than that reported by the Turkish Society of Nephrology (2.65%). This difference may arise from the high anti-HBs seropositivity rate. Conversely, the prevalence of anti-HCV seropositivity (4.3%) was similar to the mean prevalence in Turkey (4.2%). Infection prevention measures against viral hepatitis should be strictly implemented, especially in hemodialysis units.